Ultraviolet radiation of schistosoma mansoni. II. post-hatching radiation effect on some aspects of miracidia behaviour and infectivity (2000)
Batches of Schistosoma mansorti miracidia were irradiated with ultraviolet light for varying time intervals to determine the influence of radiation on the transmission potential of radiated miracidia. There was a decrease in the survival rate of hatched-free swimming miracidia that corresponded with the increasing radiation exposure time. The activity rate of radiated miracidia also decrease with increasing radiation exposure time, showing a 69.3% reduction in the mean rate of movement of miracidia irradiated for 30 minutes and 40.4% reduction in the miracidia exposed for 0.5 minutes. The infectivity rates of the free-swimming miracidia exposed to 5.0,15.0 and 30.0 minutes uv radiation were significantly different (P<0.001, dα=4.171,5.07,5.227) compared with the non- irradiated miracidium